Competency of agriculture extension agents in transfer of technology and its relationship to work performance in IADA Kota Belud, Sabah - Halim, Nur Diana (2018)
Government has established granaries area to ensure the food security and maximize the rice production in Malaysia. In order to fulfil government’s hopes, the role of extension agent in transferring technology should be focussed, mostly in their competency and work performance. A survey research was carried out at IADA Kota Belud, Sabah. The main objective of this study was to determine the competence level of extension agents in rice technology transfer based on planning, implementing and monitoring activities and work performance. Other objective was to determine the relationship between the competency of extension agent in transfer of rice technology based on planning, implementing, and monitoring activities (IV) with work performance (DV). Also, it was to find the highest independent variable contribute to work performance. This study was based on the Ice Berg’s Theory. The research involved 179 respondents from seven areas registered under IADA Kota Belud. The questionnaire distributed to the farmers was an established questionnaire which comprised of 5 sections. The data is analyzed using descriptive analysis, correlation coefficient and regression. Based on the analyzed data, the competency level of extension agents in planning, implementing and monitoring are high. Result also indicated that monitoring is highly correlated towards work performance while both planning and implementing show moderate relationship with work performance. Moreover, competency in monitoring has indicated strongest contribution which led to performance of extension agent in IADA Kota Belud. Hence, new strategy should be introduced to improve the skill along with work performance of extension agents so that they can perform well in their work.